2022
DOI: 10.3389/fvets.2022.1057079
|View full text |Cite
|
Sign up to set email alerts
|

Intra-osseous infiltration of adipose mesenchymal stromal cells and plasma rich in growth factors to treat acute full depth cartilage defects in a rabbit model: Serum osteoarthritis biomarkers and macroscopical assessment

Abstract: IntroductionIntra-articular infiltration of plasma rich in growth factors (PRGF) and adipose mesenchymal stromal cells (AMSCs) are known to inhibit osteoarthritis progression. However, in severely affected patients, the treatment cannot reach the deeper layers of the articular cartilage; thus, its potential is limited. To overcome this limitation, intra-osseous infiltrations have been suggested. The purpose of this study is to assess the impact of intra-osseous infiltration therapies on serum biomarkers of ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…However, for the criteria “vascularity” at 56- days follow up, the rabbits in TRT group showed significantly lower score, thus meaning greater presence of blood vessels, compared to CT group. These results agree with the ones previously published by our research team, in which a higher macroscopical presence of blood vessels was reported in the IO treated rabbits ( 38 ). This angiogenic activity showed in the TRT group is mainly modulated by the presence of pro-angiogenic platelet-derived vascular endothelial growth factor within the PRGF, and other mediators such as transforming growth factor-β and fibroblast growth factor-2, which produce new blood vessels by stimulating endothelial cells ( 52 54 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, for the criteria “vascularity” at 56- days follow up, the rabbits in TRT group showed significantly lower score, thus meaning greater presence of blood vessels, compared to CT group. These results agree with the ones previously published by our research team, in which a higher macroscopical presence of blood vessels was reported in the IO treated rabbits ( 38 ). This angiogenic activity showed in the TRT group is mainly modulated by the presence of pro-angiogenic platelet-derived vascular endothelial growth factor within the PRGF, and other mediators such as transforming growth factor-β and fibroblast growth factor-2, which produce new blood vessels by stimulating endothelial cells ( 52 54 ).…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, several authors have proposed IA combined with IO infiltration of PRP to provide a more comprehensive treatment to patients severely affected, and previous results have already showed that this infiltration methodology is secure and provides better and longer functional and clinical improvements compared with IA injections alone ( 28 , 34 37 , 48 51 ). Moreover, our research team has recently reported that rabbits with acute full depth chondral defect treated with IA together with IO PRGF infiltrations showed better macroscopical AC repair than those treated with single IA injections of PRGF at 56- and 84-days follow-up ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation